Studying the Effect of Human–Lactobacillus Ruteri on the Viability of Cryptosporidium Parvum - Amal Jabbar Ghaib; Amani Mohammed Jasim; Amal Aziz Kareem (Journal of Techniques)
The goal of this study was to see how well Lactobacillus ruteri probiotic bacteria might infect Cryptosporidium parvum viability at various bacterial dilutions and statuses. Cryptosporidium was obtained from stool samples of diarrheal patients and diagnosed using parasitological methods, followed by molecular methods and cell line cultivation (Human adenocarcinoma cell). The treatment of Cryptosporidium Parvum by adding Lactobacillus ruteri dilutions and status were then incubated at incubation periods (24, 48, and 72 hr), detection of Cryptosporidium count was carried out microscopically, and the parasite's viability was determined by 3-(4,5 dimethylthiazol-2-yl)-2- Diphenyltetrazolium bromide(Mtt) technique. Lactobacillus ruteri can treat Cryptosporidium parvum by suppressing activity and lowering the count with extremely significant differences, according to the findings.